Similarity Of Effects On EEG Parameters Of Aramaic, Greek Catholic And Krishnaic Prayers - Igor L. Popovych; Anatoliy I. Gozhenko; Valeriy Ye. Babelyuk; Walery Zukow; Radosław Muszkieta; Tetyana A. Korolyshyn; Galyna I. Dubkova; Ivan M. Klishch; Igor R. Mysula; Volodymyra R. Bilas; Igor-Severyn S. Flyunt; Vitaliy M. Fil'; et al. (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
The neurotropic effects of Prayer are manifested in two inhibitory and three activating patterns. The first inhibitory pattern reflects the decrease in elevated and upper limit levels of SPD of θ-and δ-rhythm in frontal loci and the second - decrease in normal SPD levels of β-and θ-rhythm in the frontal, central, temporal and parietal loci. The first activating pattern reflects a small increase in normal levels of β-rhythm index and asymmetry and SPD entropy in locus C3, as well as a further increase in elevated δ-rhythm SPD levels in loci P3 and T3. The second pattern reflects the slight increase in normal SPD levels of θ-rhythm in loci T3, T5, T6, O2 and α-rhythm in locus T5, as well as their indices and entropy SPD in locus O2. The third pattern reflects a slight increase in amplitude and SPD of α-rhythm in central, frontal, temporal and occipital loci.